Nanovoid formation induces property variation within and across individual silkworm silk threads. Issue 29 (7th April 2022) - Craig, Hamish C.; Yao, Yin; Ariotti, Nicholas; Setty, Mohan; Remadevi, Rechana; Kasumovic, Michael M.; Rajkhowa, Rangam; Rawal, Aditya; Blamires, Sean J.
Abstract : Silk is a unique fiber, having a strength and toughness that exceeds other natural fibers. Abstract : Silk is a unique fiber, having a strength and toughness that exceeds other natural fibers. While inroads have been made in our understanding of silkworm silk structure and function, few studies have measured structure and function at nanoscales. As a consequence, the sources of variation in mechanical properties along single silk fibers remain unresolved at multiple scales. Here we utilized state of the art spectroscopic and microscopic methodologies to show that the silks of species of wild and domesticated silkworms vary in mechanical properties along a single fiber and, what is more, this variation correlates with nanoscale void formations. These results can also explain the strain hardening behaviours observed in the silks where structural features of the proteins could not. We thereupon devised a predictive thermal model and showed that the voids contribute to temperature regulation within the silkworm cocoons.